COGNITIVE LINGUISTICS: FROM GENERAL PERSPECTIVES TO SOME MAJOR TENETS - Dương Hữu Biên (Tạp chí Khoa học Đại học Đà Lạt)
This article introduces Cognitive Linguistics from two different perspectives. First, the article reviews general philosophical perspectives and discusses its implications for the research themes of Cognitive Linguistics. Then the article expresses some main tenets which are adopted by cognitive linguists as guiding principles.